Ethnosemantic Toponymy of Tourist Attraction in Bangka Island - Amalia, Resti; Lubis, Donal Fernado; Bowo, Tri Arie (Pioneer: Journal of Language and Literature, 2024)
Bangka Island has several kinds of tourist attractions, such as natural tourism, historical tourism, cultural tourism and artificial tourism. The names of tourist attractions on Bangka Island still follow the names of the areas where the tourist attractions are located. Unfortunately, many local residents do not acknowledge the origins and meanings of the names of these tourist attractions. There is a need for an in-depth study regarding the naming of tourist attractions on Bangka Island to increase public awareness and the body of knowledge that needs to be preserved to increase tourism potential on Bangka Island. Research on the toponymy of tourist attractions on the island of Bangka uses ethnosemantic methods, and the results are described qualitatively. Ten tourist attractions were selected by random sampling based on the availability of information in the community. From the results of this research, it can be concluded that the names of tourist attractions on Bangka Island consist of three aspects, namely the linguistic aspect, both generic and specific, and the historical aspect of the formation and dynamics of society in the area.